Menganalisis Masalah Usaha Mengenai Perilaku Karyawan dan Cara Mengatasi Masalah di Kga.Creative - Lenta Octafianis Fau; M. Iqbal Ramadhan; Melan Anggia Putri; Muhammad Adha; Vivi Nila Sari (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This study aims to analyze the problems faced by this business in the last few months and analyze employee behavior that appears in the work environment and identify effective strategies to overcome these problems. The research method used includes direct observation, namely interviews with employees. The research results show that factors such as less effective communication and lack of equipment facilities in a business. To overcome this problem, it is recommended to repair internal communication channels and equip all the necessary equipment.